Nigeria - Lemieux, Diane (London : Kuperard, 2012)
A guide to the customs and culture of Nigeria, providing information on the country's land and people, values and attitudes, customs and traditions, lifestyles, friendships sports and recreation, travel, health, business etiquette, and communication.
Map of Nigeria -- Introduction -- Key Facts -- Chapter 1-Land and People -- Chapter 2-Values and Attitudes -- Chapter 3-Customs and Traditions -- Chapter 4-Making Friends -- Chapter 5-The Nigerians at home -- Chapter 6-Time Out -- Chapter 7-Travel, Health, and Safety -- Chapter 8-Business Briefing -- Chapter 9-Communicating -- Further Reading -- Index -- Acknowledgments.
Includes bibliographical references (page 165) and index.
Keywords: Nigeria -- Social life and customs; Etiquette -- Nigeria; National characteristics, Nigerian